PENERAPAN STRATEGI PEMBELAJARAN AKTIF PRACTICE-REHEARSAL PAIRS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 2 PEKANBARU - Marta Marta; Erviyenni Erviyenni; Herdini Herdini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research on the application of active strategies Practice-Rehearsal Pairs have been conducted to determine whether application of active strategies Practice-Rehearsal Pairs can improve student achievement on the Colloid subject in class XI SMAN 2 Pekanbaru. The research’s form is an experimental research with pretest-posttest design. The research was conducted on the even semester in academic year 2014/2015. The sample consisted of two classes, class XI Science 1 as the experimental and class XI Science 2 as the control class which randomly selected after tests of normality and homogeneity. Experimental class was treated by given a strategies Practice-Rehearsal Pairs, while the control class was not given strategies Practice-Rehearsal Pairs. Data collection technique use this the test. Data analysis technique use this the-test. Based on the results of the final data processing obtained tcount> ttable, it is 2,560 > 1,669. This shows that the application of active strategies Practice-Rehearsal Pairs can improve student achievement on the Colloid subject in class XI Science SMAN 2 Pekanbaru, the effect of an increase of 9,49%.Keywords: Colloid, Active Strategies, Learning Achievement, Practice-Rehearsal Pairs.